Smart classroom environments affect teacher-student interaction: Evidence from a behavioural sequence analysis - Zhan, Zehui; Wu, Qianyi; Lin, Zhihua; Cai, Jiayi (Australasian Journal of Educational Technology, 2021)
This study investigated the effect of classroom settings on teacher-student interaction in higher education by comparing the behavioural sequences in smart classrooms (SCs) and traditional multimedia classrooms (TMCs). Twenty in-classroom teaching sessions were randomly selected from six universities in South China, involving 1,043 students and 23 teachers. Half of the sessions were taken in SCs as the experimental group, and half were in TMCs as the control group. A teacher-student interaction behaviour coding schema was developed, and a total of 17,805 observable behaviours were collected and coded sequentially via a review of classroom videos. Then, the behavior pattern diagram was set up to visualise a lag sequential analysis results by four themes, namely teacher-talk, teacher-action, student-talk and student-action. Results show that compared to TMCs, the SCs triggered significantly more self-initiated student actions and student-driven teacher talk, while teacher-initiated talk decreased significantly, indicating that students’ autonomy was strengthened in the SC. Furthermore, teachers’ workload was somewhat reduced, and they obtained more support with trying new pedagogies with mobile terminals in the data-rich environment. These findings provide evidence to validate the effect of SCs on increasing teacher-student interaction and strengthening the students’ dominant position.